Alexandru MATEI, Christian MORARU & Andrei TERIAN (eds.).— Theory in the “Post” Era. A Vocabulary for the Twenty-First-Century Conceptual Commons. New York et al.: Bloomsbury Academic, 2022, 376 pp. - Iliescu Gheorghiu, Catalina (Signa: Revista de la Asociación Española de Semiótica, 2023)
Reseña